Insetos à deriva em riachos neotropicais. - Guidi, Claudia Roberta (2013)
The investigation of diurnal and nocturnal variation of community structure of immature insects drifting becomes necessary due to the lack of studies in neotropical streams. The hypothesis of this study is that higher density of immature insects and larger sizes of Ephemeroptera occur at night, as a mechanism to avoid predation. The samples were collected in spring and summer, during the day and night period, in two streams pertaining to the Basin Pirapó River, southern Brazil. Aquatic insects were collected with a net drift. We recorded 73 taxa of insects drifting in both streams. The beta diversity showed little change in the composition of invertebrate drift between periods investigated. The greater richness and density was recorded at night, as well as larger sizes of Baetidae (Ephemeroptera). Significant differences were observed in the density of Ephemeroptera and Trichoptera between the two periods, with higher abundance at night. The drift behavior of some insects is, probably, related to the pressure exerted by the various streams of these predators that consume insects in their diet. Further research is needed to elucidate which groups of insect the behavior of the drift is conditioned to predation and which groups the abiotic factors are most important.